The Effectiveness of Authentic Assessment in Assessing Students’ Writing Skill - Windi Arianda; Endang Komariah; Burhansyah Burhansyah (Research in English and Education Journal, 2021)
The aim of this study is to find out the effectiveness of authentic assessment in assessing students’ writing skill and which kind of authentic assessment is effective in assessing students’ writing skill. This study was in the form of library research. Thus, the source of data for this study is related theories about authentic assessment. In addition, previous studies and research are also included into the data sources.  The instrument of this research was in the form of documents such as journals, books, scripts, and others which discuss authentic assessment. In term of data analysis, the writer used a conclusion drawing technique to analyze the available data from the source of data. Based on the document analysis, the implementation of authentic assessment is categorized as effective in the process of assessing students’ writing skill because of several reasons namely; contextual, objectivity rather than subjectivity, student-centered rather than teacher-centered, and stimulating needed skills for students’ real-life. The analysis also showed that the implementation of portfolio technique overcomes the problems faced by teacher in the teaching writing skill.